Metaphor Processing Dysfunctions in Schizophrenia Patients With and Without Substance Use Disorders - Karabanowicz, Ewa; Tyburski, Ernest; Karasiewicz, Karol; Sokołowski, Andrzej; Mak, Monika; Folkierska-Żukowska, Monika; Radziwiłłowicz, Wioletta (Frontiers in Psychiatry, 2020)
Background: Patients with schizophrenia have difficulties comprehending metaphors, which significantly impedes communication. However, this topic has not been thoroughly studied in people with a dual diagnosis. On this basis, we formulated two research aims: a) to compare the ability to comprehend metaphors in schizophrenia patients without (SZ) and with substance use disorder (SZ-SUD) and b) to determine the relationship between the processing of metaphorical content and the severity of psychopathological symptoms in both clinical groups. Methods: A total of 40 individuals with SZ and 40 individuals with SZ-SUD took part in the study. The control group was composed of 40 individuals without a psychiatric or neurological diagnosis. Four subtests from the Right Hemisphere Language Battery (Picture Metaphor Test, Written Metaphor Test, Picture Metaphor Explanation Test, Written Metaphor Explanation Test) were used to measure the ability to understand and explain metaphors. Results: Both groups of individuals with schizophrenia (SZ and SZ-SUD) scored lower than individuals from the control group on all tests of metaphor processing. However, no differences were observed between the two clinical groups. SZ-SUD patients had better results for Picture Metaphor Explanation than for Written Metaphor Explanation. Negative symptoms were found to be significant predictors of difficulties with understanding and explaining metaphors. Conclusion: Individuals with schizophrenia, regardless of their substance use disorder (SUD) status, exhibit impaired metaphorical content processing. SUD in schizophrenia is not associated with significant impairments in understanding and explaining metaphorical content. Moreover, impairments in processing metaphorical content are associated with more severe negative symptoms of schizophrenia.